Facilitating a group resonance intervention with a volleyball team: An exploration of the process between a consultant, coach, and athletes - Callary, Bettina (University of Ottawa (Canada), 2007)
Resonance interventions are aimed at developing awareness of how one wants to feel, how to prepare to feel this way, the obstacles that get in the way of that desired feel, and how to reconnect with it through individual or group sessions led by a consultant (Newburg, Kimiciek, Durand-Bush, & Doell, 2002; Arcand, Durand-Bush, & Miall, 2007). The purpose of this study was to examine how a coach developed and applied the process of resonance with his team through a resonance intervention facilitated by a researcher/consultant and continued nurturing this process once the intervention was completed. The participants included a varsity volleyball team comprising a 39 year old male coach and 16 female athletes aged between 18-24 years. The 26-week study comprised three phases: a 6-week pre-intervention phase involving interviews and observations; a 14-week intervention phase involving four team sessions, individual consultations with the coach, participant journaling, and observations; and a 6-week post-intervention phase involving interviews. The results are presented as a narrative (Polkinghorne, 1995) to tell the story of how the researcher/consultant worked with the team as a group and also individually with the coach to help them learn and apply their personal resonance process and enhance their performance, leading them to a OUA Championship title.
Keywords: Health Sciences, Recreation.